Withdrawal from long‐term methamphetamine self‐administration 'normalizes' neurometabolites in rhesus monkeys: a 1H MR spectroscopy study. (4th August 2013) - Yang, Shaolin; Belcher, Annabelle M.; Chefer, Svetlana; Vaupel, D. Bruce; Schindler, Charles W.; Stein, Elliot A.; Yang, Yihong
Abstract 1H magnetic resonance spectroscopy has demonstrated alterations in several neurometabolites in methamphetamine (METH)‐dependent individuals in brain regions implicated in addiction. Yet, it is unclear whether these neurochemicals return to homeostatic levels after an individual abstains from drug use, a difficult question to address due to high recidivism and poor study retention in human subjects. We thus utilized a non‐human primate model of addiction to explore the effects of long‐term drug exposure and withdrawal on brain neurochemistry. Ten rhesus macaque monkeys on an active METH self‐administration protocol (average use 4.6 ± 0.8 years, average daily intake between 0.4 and 1.2 mg/kg) and 10 age‐ and sex‐matched drug‐naive controls (CONT) served as subjects. Concentrations of several neurochemicals were evaluated at several timepoints following withdrawal from drug availability (10 monkeys at 1 week and 1 and 3 months, and 6 monkeys at 6 and 12 months; CONT examined at one timepoint). At 1 week following METH withdrawal, we found increases in myo‐inositol in anterior cingulate cortex in the METH group relative to CONT. These alterations showed a linear pattern of decreased levels ('normalization') by 1 year of abstinence. We also found decreases in glutamine and Glx (composed mainly of glutamate and glutamine) in the caudate‐putamen of the same animals at early withdrawal that showed a similar linear pattern of increasing concentration by 1 year. These results demonstrate that despite protracted, long‐term use, neurochemical changes seen following long‐term drug administration do not persist following prolonged abstinence, suggesting therapeutic effects of long‐term withdrawal from drug use.